2015
DOI: 10.3791/53083
|View full text |Cite
|
Sign up to set email alerts
|

A Screenable <em>In Vivo</em> Assay for Mitochondrial Modulators Using Transgenic Bioluminescent <em>Caenorhabditis elegans</em>

Abstract: The multicellular model organism Caenorhabditis elegans is a small nematode of approximately 1 mm in size in adulthood that is genetically and experimentally tractable. It is economical and easy to culture and dispense in liquid medium which makes it well suited for medium-throughput screening. We have previously validated the use of transgenic luciferase expressing C. elegans strains to provide rapid in vivo assessment of the nematode's ATP levels.1-3 Here we present the required materials and procedure to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Lagido et al, in the Glover and Pettitt laboratories, developed a luciferase expressing strain that allowed in vivo assessment of relative ATP levels in C. elegans (Lagido et al 2008). They later described the use of this strain for monitoring toxicant effects on mitochondrial function (McLaggan et al 2012;Lagido et al 2015). Members from the Meyer laboratory extended the use of this strain to allow rapid evaluation of the effects of toxicants on mitochondrial function, particularly the electron transport chain, glycolysis and fatty acid oxidation (Luz et al 2016b).…”
Section: Toxicologymentioning
confidence: 99%
“…Lagido et al, in the Glover and Pettitt laboratories, developed a luciferase expressing strain that allowed in vivo assessment of relative ATP levels in C. elegans (Lagido et al 2008). They later described the use of this strain for monitoring toxicant effects on mitochondrial function (McLaggan et al 2012;Lagido et al 2015). Members from the Meyer laboratory extended the use of this strain to allow rapid evaluation of the effects of toxicants on mitochondrial function, particularly the electron transport chain, glycolysis and fatty acid oxidation (Luz et al 2016b).…”
Section: Toxicologymentioning
confidence: 99%
“…A sharp decline in bioluminescence (maximal inhibition) relative to controls occurred at the lowest rotenone concentration of 2.5 μM. This decline in bioluminescence was consistent with reduced cellular ATP (Lagido et al, 2015). The results obtained from C. elegans exposed to rotenone suggested that chronic exposure to low concentration (2 or 4 μM) caused mitochondrial damage through persistent suppression of mitochondrial biogenesis and mitochondrial gene expression leading to mitochondrial dysfunction that contributed to DA neuron degeneration (Zhou et al, 2013).…”
Section: Evidence Supporting Applicability Of This Relationshipmentioning
confidence: 55%
“…As we were primarily interested in investigating the effects of mtDNA knockdown on somatic tissues, and development of the nematode germline during the L3/L4 transition is associated with large increases in mtDNA copy number [19, 38] which would confound the interpretation of our results, we used the germline-deficient, in vivo ATP reporter strain PE255 glp-4 for all experiments [22, 23]. EtBr, a well-known inhibitor of mtDNA replication [3941] that is frequently used to generate rho 0 (mtDNA-deficient) cells, was used to reduce mtDNA copy number in nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo steady-state ATP levels were determined as previously described [23], and as visualized in [22]. Briefly, 50 nematodes (suspended in K-medium) were loaded into each well of a white 96-well plate (four wells per treatment), and then GFP fluorescence was measured (emissions filter: 502nm; excitation filter: 485nm) using a FLUOstar Optima microplate reader (BMG Labtech, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation